Pharmacology and chemistry of Myristica fragrans Houtt. - a review - Geetha, P Pushpangadan, S Rajasekharan, P G Latha, P G Sindhu, S R Suja, B S (Journal of Spices and Aromatic Crops, 2005)
The information available on the pharmacology and chemistry of nutmeg (Myristica fragrans) has been reviewed and the areas of interest for further investigation have been suggested.